Performance bounds on the localization of cellular phones using RSS measurements with unknown pathloss exponents - Sarı, Veli. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
In this thesis, performance of an Received Signal Strength (RSS) based location estimation model, which incorporates the antenna radiation pattern information into log-normal path loss the signal model is evaluated. Performance bounds evaluated with most common technique called Cramer-Rao Lower Bound(CRLB) which puts a lower bound on the variance of a parameter estimate that can be achieved by any unbiased estimator. Being able to place a lower bound on the variance of any unbiased estimator proves to be extremely useful in practice. It provides a benchmark against which we can compare the performance of any unbiased estimator. Furthermore, it alerts us to the physically impossibility of nding an unbiased estimator whose vairance is less than the bound. The Performance analyzing is done under various scenarious and solutions showed that this model is very robust against the variations in the signal propagation characteristics and it can be very useful in radio planning of cellular networks.
Keywords: Wireless communication systems.; GPS receivers.